What does peer-to-peer lending evidence say about the risk-taking channel of monetary policy? - Yiping Huang; Xiang Li; Chu Wang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
This paper uses loan application-level data from a peer-to-peer lending platform to study the risk-taking channel of monetary policy. By employing a direct ex-ante measure of risk-taking and estimating the simultaneous equations of loan approval and loan amount, we are the first to provide quantitative evidence of the impact of monetary policy on the risk-taking of nonbank financial institution. We find that the search-for-yield is the main workhorse of the risk-taking effect, while we do not observe consistent findings of risk-shifting from the liquidity change. Monetary policy easing is associated with a higher probability of granting loans to risky borrowers and a greater riskiness of credit allocation, but these changes do not necessarily relate to a larger loan amount on average.
URN:NBN:fi:bof-201908291433
Keywords: E52; G23; 330; Monetary Policy; Risk-taking; Nonbank Financial Institution; Peer-to-Peer Lending; Search-for-yield; Risk-shifting